Analysis of Students’ Speaking Anxiety in EFL Classroom - Putri, Hadriyanti Eka; Muhayyang, Maemuna; Aeni, Nur (Journal of Excellence in English Language Education, 2024)
This study was carried out to investigate the types of students’ speaking anxiety in EFL classroom. This research used qualitative descriptive research. The subject of this study was six students from the third semester of the English Education Department Class C batch 2021, State University of Makassar. They were recruited using a purposive sampling technique. This study used observation and interview as the research instruments. The interview was used to determine the types of students’ speaking anxiety in EFL classroom and the observation was used to support the interviews’ data. It is concluded that oral presentation, limited vocabulary, fear of making mistakes, lack of preparation, and lecturer’s personality and attitudes were the main factors that contributed to students’ speaking anxiety in EFL classroom. The results of this study established that most students experienced test anxiety and fear of negative evaluation as the types of their speaking anxiety.